APPLYING AN INCLUSIVE DEFINITION OF PHYSICAL ACTIVITY TO UNDERSTAND STABILITY AND CHANGE IN OLD AGE. (11th November 2018) - Notthoff, N; Deeg, D J H; Visser, M; van Schoor, N; Huisman, M; Gerstorf, D
Abstract: Findings that older adults are not sufficiently physically active are largely based on cross-sectional comparisons with a narrow definition of physical activity. Using data from the Longitudinal Aging Study Amsterdam (n=2, 486, age range 54–104 years, M=72, SD=9.08; 50% women), we examined how the proportional contribution of eight activity domains (e.g., structured sports, household work, walking for transportation) to total activity time changed with increasing age and investigated the role of sociodemographic, psychological, and environmental factors including gender, self-efficacy, and urbanization. Low-intensity activities for mastering daily life (e.g., light housework) increased in importance with age; they were affected by sociodemographics and health. Higher intensity activities (e.g., heavy housework) tended to decline; they were influenced by sociodemographics. Other activities (e.g., structured sports) remained stable at low frequencies; they were shaped by sociodemographics and external factors. Differentiating activities by purpose may contribute to better understanding age-related trajectories and identifying relevant predictors.